She was choked by a corset or a fashion trend of the past, the consequences of wearing and its modern counterpart - Ruzieva Zumrad (Genius Publishing Group, 2023)
This article examines the history of the corset from antiquity and the Victorian era to the present day, describes the consequences of wearing a corset from the point of view of medicine and common sense, tells the creative activity of designers and brands that used corsets in their collections.
Keywords: Fashion; style; history; corset